PERSEPSI ANAK TERHADAP TAYANGAN IKLAN THREE VERSI “INDIE” - Hasanah, Ratih; Andriani, Dian (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2015)
This article investigates the perception of Children towards a telco brand ad, Three, version “Indie” (“If I am already big”). The study took four primary informants, namely children in the Learning Community of Qur'an Lovers' Homes (RSPQ) located on Jalan Sukabirus Gg. Islam 3, 13 E, Citereup Village Dayeuh Kolot Subdistrict, Bandung, while secondary informants are child psychologists. Using a qualitative approach, data collected through observation, in-depth interviews, and review literature, while data analyzed using Miles and Huberman’s model. The study uses the perceptual theory of Stimulus-Responses, and the results show that in the process of forming perception, children begin with positive attention. They can interpret information well and also gain knowledge about brand messages conveyed in advertisements. However, the perception they get is not strong because the environment around them does not support it. To cite this article (7th APA style): Hasanah, R. & Andriani, D. (2015). Persepsi Anak Terhadap Tayangan Iklan Three Versi “Indie” [Perception of Children towards the Three Ad]. Journal Communication Spectrum, 5(1), 13-25.